Pelatihan Sistem Informasi Manajemen Induk Sinode GKS - Fajar Hariadi; Arini Aha Pekuwali; Yustina Rada; Desy Asnath Sitaniapessy; Rambu Yetti Kalaway; Raynesta Mikaela Indri Malo; Itha Priyasthiti; Pingky Alfa Ray Leo Lede; Reynaldi Thimotius Abineno; Leonard Marten Doni Ratu; Ferdian Fendi Djami; Umbu Theofilus Dendimara; Demaris Lemba Oy; Papy Rivandi Bara; Trisari D. N. B. Mira; Riwa Rambu Hada Enda (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Training on the Sistem Informasi Manajemen Induk Sinode GKS was conducted as part of the digitalization initiative for congregation and financial data management within Gereja Kristen Sumba (GKS), under the auspices of Sinode GKS. The training was attended by 83 participants, consisting of secretaries, church council working bodies, and treasurers responsible for managing congregation data as well as financial administration and reporting in GKS churches under the Sinode.  User evaluations (on a scale of 1 to 5) of the Sistem Informasi Manajemen Induk Sinode GKS (Simanis V.2) yielded a score of 3.95 for the congregation data management feature and 3.47 for the financial management feature. These results indicate that both the training and the Simanis application have supported the churches' needs in managing congregation and financial data, although improvements to certain features are still necessary.